Trends in comparative law and economics - Garoupa, Nuno (Anthem Press, 2022)
The book is a short introduction to comparative law and economics, a growing field in the interaction between law, economics and comparative political science. It is a guide to economists, lawyers and political scientists looking for a brief overview. It includes both strands of the traditional literature, namely the role of legal families and microeconomic analysis of legal rules in a comparative perspective. The study of courts at the global level is complemented by comparative judicial politics.